2018
DOI: 10.1021/acsomega.8b02046
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies on Dual Role of Natural Flavonoids in Detoxification of Lead Poisoning: Bench-to-Bedside Preclinical Trial

Abstract: Ubiquitousness in the target organs and associated oxidative stress are the most common manifestations of heavy-metal poisoning in living bodies. While chelation of toxic heavy metals is important as therapeutic strategy, scavenging of increased reactive oxygen species, reactive nitrogen species and free radicals are equally important. Here, we have studied the lead (Pb) chelating efficacy of a model flavonoid morin using steady-state and picosecond-resolved optical spectroscopy. The efficacy of morin in prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 59 publications
0
37
1
Order By: Relevance
“…Several studies have shown that serum aminotransferase activity as sensitive indicators of liver injury. Damage to the hepatic cells alters their membrane permeability, which leads to the leakage of enzymes from the cells . As described in Table , three weeks of Pb(II) exposure significantly enhanced the AST and ALT levels by 5.7‐fold and 5.2‐fold, respectively, compared to control ( p <0.001).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Several studies have shown that serum aminotransferase activity as sensitive indicators of liver injury. Damage to the hepatic cells alters their membrane permeability, which leads to the leakage of enzymes from the cells . As described in Table , three weeks of Pb(II) exposure significantly enhanced the AST and ALT levels by 5.7‐fold and 5.2‐fold, respectively, compared to control ( p <0.001).…”
Section: Resultsmentioning
confidence: 87%
“…[Q] is the quencher concentration, K D denotes the SV quenching constant, k q the bimolecular quenching rate constant, τ 0 is the fluorescence lifetime of the fluorophore . The linearity in the SV plot (Figure C‐inset) indicates a single type of quenching, either static or dynamic . To, identify the nature of quenching, we repeated the experiments at three different temperatures (300 K, 310 K, and 320 K).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations